Causal nihilism and science - Vospernik, Miklavž (2006)
One of the major lines of argumentation for causal nihilism is based on the allegedly sound argument which claims that causality plays no role in advanced sciences, such as physics, and thus is only an anthropocentric projection deriving from our common-sense apprehension of daily life (e. g. Russell, or Mach). In this article we shall argue against Russell's version of the argument which is based on the premise that mature scientific laws are expressible as mathematical formulae and thus lack any causal content. In particular, we shall argue that even if we took scientific laws to be expressible as mathematical formulae and thus capable of being stated in an entirely symmetrical form (in other words having no preferences as to what could be causes and what their effects), there would still be an asymmetry in their conditionals, and we would have to account for it. The most natural way to do this, and this is because physics itself so dictates, is to invoke causality which automatically provides the required asymmetry. Thus we may conclude that physics' causal lore does distinguish physics from what is merely mathematically possible, and so it is unjustified and wrong to ban causality from science.
Bibliografija: str. 274.
Keywords: filozofija -- vzročnost -- kavzalni nihilizem -- znanost; philosophy -- causality -- causal nihilism -- science